A Cross‐National Look at How Welfare States Reduce Inequality. Issue 2 (4th February 2013) - Moller, Stephanie; Misra, Joya; Strader, Eiko
Abstract A major shift in welfare state research occurred at the turn of the century as researchers moved from explaining the development of welfare states and variations in spending across welfare states to a focus on welfare state outcomes. One of the key outcomes examined in the literature is inequality. While much of the early literature examined overall spending, followed by analysis of specific taxes and transfers related to old age, unemployment, disability, health, and families, more recent research has included a broader range of welfare state policies including work‐family policies and flexicurity. This essay highlights some important developments in the research on welfare states and inequality.